2013
DOI: 10.1111/jgh.12098
|View full text |Cite
|
Sign up to set email alerts
|

Is narrow band imaging superior to high‐definition white light endoscopy in the assessment of diminutive colorectal polyps?

Abstract: NBI was as accurate as hWLE in differentiating diminutive colorectal polyps. Once a learning curve was reached, NBI achieved significantly higher accuracies with good interobserver agreement. Using a simplified classification, a didactic learning session and feedback on performance, diminutive colorectal polyps could be predicted with high accuracies with NBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…White light endoscopy (WLE), has been a standard technique for diagnosis of disease pathology in the upper and lower part of the gastrointestinal (GI) tract for several decades 1 2 . However, until recently, the small bowel was an obscure region requiring invasive intervention for diagnosis and treatment.…”
mentioning
confidence: 99%
“…White light endoscopy (WLE), has been a standard technique for diagnosis of disease pathology in the upper and lower part of the gastrointestinal (GI) tract for several decades 1 2 . However, until recently, the small bowel was an obscure region requiring invasive intervention for diagnosis and treatment.…”
mentioning
confidence: 99%
“…[7][8][9] Selfdirected, computer-and Web site-based training modules have been combined with ongoing self-directed feedback and were found to be effective in teaching NBI for characterizing colon polyps and gastric lesions. 10,11 However, most of these studies have assessed ex vivo performance. Those that have assessed in vivo performance have found that the training programs improve learner performance, but have not consistently shown that learners can reach all the established performance thresholds.…”
Section: Trainingmentioning
confidence: 99%
“…A wide variety of learning tools has been described, including classroom type[6], self-directed computer-based[3] or web-based teaching programs[7]. Still pictures, videos or both have been used to explain the optical features of each type of polyp[8,9]. However, there are no head-to-head comparisons between learning tools and most of them have not been validated.…”
Section: Introductionmentioning
confidence: 99%